Phytochemical and Hplc Profiling Of Extracts from Fingerroot (Boesenbergia Rotunda) Rhizomes - Yap, Amy Li Ching (2008)
Boesenbergia rotunda (L.) Mansf. Kulturpfl. is a perennial herb belonging to the Zingiberaceae family. It is commonly used in Southeast Asia as food ingredient and in folk medicine treatment of several diseases. In this research, six flavonoid derivatives, pinostrobin (3), pinocembrin (5), alpinetin (4), cardamonin (6), boesenbergin A (18) and sakuranetin (12) were isolated from the rhizomes of Boesenbergia rotunda using various extraction techniques such as normal soaking, soxhlet extraction, partition method and microwave-assisted extraction (MAE). All of the compounds were elucidated based on their spectroscopic data and by comparison with the previous works. Extraction techniques including microwave-assisted extraction (MAE) have been applied in this research to obtain extracts from the rhizomes of Boesenbergia rotunda. Microwave-assisted extraction (MAE) is a good and reliable alternative to conventional extraction methods as the microwave-assisted extraction takes lesser extraction time compared to conventional methods. The consumption of solvent for extraction is also reduced. A High Performance Liquid Chromatography (HPLC) profiling has been developed based on the distribution and contents of chemical constituents from different extraction techniques. In addition, the extraction efficiencies of different methods towards the chemical constituents have also been compared. The fresh rhizomes of Boesenbergia rotunda was subjected for conventional hydrodistillation and microwave-assisted hydrodistillation (MAHD) to obtain essential oils. The composition of Boesenbergia rotunda essentials oil isolated from conventional hydrodistillation and microwave-assisted hydrodistillation were quite similar. The main components were eucalyptol, camphor, α-citral, β-linalool and methyl cinnamate. In the essential oil obtained from conventional hydrodistillation, the major compound was trans-geraniol (20%) whereas the major compound for microwave-assisted hydrodistillation oils was α-citral (40%). As for the antimicrobial screening, the hexane extract showed moderate activity against Staphylococcus aureus (MRSA) (Gram-positive), while the chloroform extract showed weak activity against Pseudomonas aeruginosa (Gram-negative). Cytotoxic screening showed most of the extracts and pure compounds isolated from the rhizomes of Boesenbergia rotunda were active against HL-60 cancer cell line. The chloroform and hexane extracts showed strong activity with IC50 values of 5.8 μg/mL and 8.5 μg/mL, respectively while the essential oil showed moderate activity with IC50 values of 14.0 μg/mL. As for the pure compounds, boesenbergin A (18) showed the most potent cytotoxic activity with IC50 value of 5.8 μg/mL. In the cytotoxic screening against MCF-7 cancer cell line (human breast cancer), the chloroform extract is the only extract showed weak activity with the IC50 value of 23.3 μg/mL. In addition, sakuranetin (12) also showed weak activity with IC50 value of 22.5 μg/mL. All extracts and pure compounds were inactive except both hexane and chloroform extracts in the cytotoxic screening against HT-29 cancer cell line (human colon cancer). The hexane and chloroform extracts showed weak activity with the IC50 value of 21.1 μg/mL and 20.0 μg/mL, respectively.